Vyadhikaraṇam : Caturdaśalakṣaṇī - Gaṅgeśa (Kendrīyasaṃskr̥tavidyāpīṭhagranthamālā, 1985)
Basic work, with commentary and supercommentary, of neo-Nyaya school in Indic philosophy; portion of Tattvacintāmaṇi dealing with definitions of invariable concomitance (vyāpti).